EFFECTIVENESS OF PLAYING ORIGAMI AND PUZZLE IN MOTORIC DEVELOPMENT ON 4 – 5 YEARS OLD CHILDREN AT KEMALA BHAYANGKARI KINDERGARTEN 38 PURWODADI GROBOGAN - Ni Made Sri Budhi Utami; Sulistyarini (The Shine Cahaya Dunia D-III Keperawatan, 2019)
Background; Fine motor delay is a common problem in pre-school children. Children withfine motor delay in KemalaBhayangkari kindergarten are about 32 children. AccordingDelgado (2016) 12-18% of children's population in developing countries show significantdelay in psychomotor ability resulting behavior problems and difficulty in learning process.One of the strategies that can be used to train fine motor development is to play origami andplay a puzzle. The purpose of this research is to know effectiveness of playing origami andplaying puzzle in fine motor development on 4 – 5 years old children in Kemala BhayangkariKindergarten 38 Purwodadi - Grobogan Method; The research design thatwas used in this study was Quasi Experimet with PosttestOnly Control Group Design approach. The sampling technique was Probability samplingwith random sampling method (simple random sampling) with 32 respondent. Result; Based on the analysis using SPSS 16.0, the average value for development speedafter being treated with origami is 6.19 days, while for the speed of development after beingtreated with puzzle is 8.13 days. In addition, from Mann-Whitney test, ρ value is 0.003 (α =0.05) which shows the difference of effectiveness of playing origami and playing puzzledealing with the development of fine motor. Conclusion; From the results of the above research it can be concluded that there aredifferences between the effectiveness of playing origami and playing puzzle dealing with finemotor development on 4-5 years old children.